Integration of Learning, Innovation, and SDGs Value in Pesantren: Sustainable Islamic Education Development - Fitria Martanti; Ma’as Shobirin; Maskur; Moch Fatkhurronji; Ana Surjanto (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to examine the implementation of learning innovations and the integration of Sustainable Development Goals (SDGs) values in the Darul Ilmi Islamic Boarding School, as well as the strategies used in dealing with the digital era and the challenges that arise during the integration process. Theoretical framework: The theoretical framework of this research is based on the concept of sustainable Islamic education that integrates global values (SDGs), local wisdom, and Islamic principles as a foothold in the development of an Islamic boarding school education system that is adaptive to the changing times. Literature review: The literature review includes studies on pesantren education innovations, the integration of SDGs values in the learning system, and the transformation of sustainability value-based education, which is still limited, especially in the context of children's pesantren. Methods: This study uses a qualitative approach with data collection techniques in the form of in-depth interviews, direct observation, and documentation. The main informants consist of pesantren caregivers, accompanying teachers, and students who are selected purposively. Data analysis was carried out using the Miles and Huberman model: data reduction, data presentation, and a conclusion drawn. Results: The results show that SDGs-based learning innovations are implemented through contextual approaches that combine global, local, and Islamic values. This innovation has a positive impact on the quality of learning and social relevance of Islamic boarding schools, as well as improving the image of Islamic boarding schools in the community. Implications: Providing an adaptive and sustainable model of Islamic education in responding to global challenges. Novelty: Offers a new study on the integration of SDGs in children's boarding schools, which is still rarely discussed scientifically.